Papers - Theoretical - Relation between Spontaneous Polarization Curves and Depth, Size and Dip of Ore Bodies (T. P. 1536) - Walter Stern (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1946)
The self-potential or spontaneous polarization method is one of the oldest in the field of electrical exploration. When applied in prospecting for ore bodies, it is one of the most rapid and inexpensive means of locating indications of ore bodies at shallow depth. Usually, the procedure is to survey the equipotential lines of the electrical field that is generated by the electrochemical activity of the ore near the ground-water level, and to localize the so-called negative centers or points of greatest negative anomaly. Another field procedure involves the measurement of potential differences along potential profiles, generally laid out at right angles to the assumed strike. Again, in such survey, the basis for establishing the presence of ore is the location of negative potential anomalies. The earlier writers on the subject, notably Schlumbergerl and R. C. Wells,2 did much to clarify the fundamental electrochemical phenomena involved. Interpretation of the field data, however, remained largely qualitative. In 1925, A. Petrovsky3 analyzed the relation between the shape of the potential anomaly curve and size and depth of an Ore body by assuming the subsurface body to be a polarized sphere.' Along similar lines of approach, Edge and Laby5 considered the ore body a dipping sheet with limited extent in the direction of strike, while Poldini6 based the theory on the assumption of a dipping bar. The following study endeavors to enlarge upon these earlier investigations and attempts, on the basis of the potential distribution of a polarized bar, to indicate certain characteristics of the anomaly curve that make possible the determination of depth, size and dip of a subsurface body. The Spontaneous Polarization Field Set Up by an Ore Body If a sulphide ore body is subjected to oxidation varying in degree in its upper and lower parts according to the difference in the concentration of oxygen within the surrounding medium, an electrical potential field is set up. The form and distribution of this field will be investigated herein with special reference to its components on the earth,s surface. Under the simplifying assumption that the ore body may be considered as a dipole with the point sources Q1 and Q2 situated at its upper and lower ends (Fig. I), the potential of the spontaneous polarization at point P is given by the following equation: